Winning and Nominated Picture Books From the Večernica Award Collection - Haramija, Dragica; Batič, Janja (Trideset let literarne nagrade večernica, 2026)
The chapter presents all eighteenpicture books that were awarded or nominated for the Večernica Award over the Award's thirty-year history. In the first part, we analysed the picture books in terms of their topics and the literary genres they represent. In the second part, a multimodal analysis of the picture book How to Hug a Hedgehog examines the influence of the illustrations on the summative meaning of the picture book. The findings of the content analysis showed that short prose and poetry were represented among the nominees. Short fantasy stories dominated the short prose works. The thematic analysis revealed two dominant themes, namely various human relationships and the lives of anthropomorphically portrayed animals. The results of the multimodal analysis of the selected picture book demonstrated that illustrations in a picture book significantly contribute to the way the topic is presented and developed. The influence of the illustrations on shaping the theme, the mood, the literary characters, etc., was also evident in the other nominated picture books.